(3GdHRGRjI aj GdaJGhis - (3GdHRGRj, eMeO Hf eMeO Hf TgGH, J (B827 (3g`s
(3ChdgG (B:s
(3MeOG def OYi Edi OGQ GdSdGe hHYO agPGeNJUQ aj HjGf JYQjaGJ GdCMcGe Ydi hLg GdEJbGf hGdEMcGeeYg GdYHO eMeO Hf eMeO GdcQOj PGcQG ajg NdGUI fhGRd GdCjGe heNJGQGJ GdeTGjN GdcQGe s
(3BNQgG (B:s
(3cJGH GdOYhi hajg SJI YTQ aUdG , GdChd aj eYQaI GdNUe hGdJfGbV hGdOaY heSGFd gPG GdLfS Ydi GdJeGe fPcQ aj GdNGeS YSQ Ef TGA Gddg GdcQjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 646s
(3cTa GdXfhf (B1 / 242s
(3TPQGJ GdPgH (B7 / 183s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs